Business incentives for local economic development - Maša Trinajstić; Marinela Krstinić Nižić; Nada Denona Bogović (Economies, 2022)
The main role of local development policy is to create a favorable business environment and new jobs, thus contributing to economic development. Creating a positive business environment to act as a pull factor for new businesses is of great importance, because entrepreneurship conduces to the rise in the supply of goods and to an increase in citizens' income and revenues of local budgets. This paper therefore examines the main goals of economic development in the towns and municipalities of the Republic of Croatia, as well as the tools used by local governments to encourage entrepreneurship and new businesses. Using a questionnaire, mayors and deputies of towns and municipalities were surveyed, and the sample covered 131 towns and municipalities. The research methodology included a descriptive analysis and the Kruskal-Wallis test. The results indicate that improving the quality of life of the residents, creating new jobs, and retaining the residents in the town or municipality were identified as the most important goals of economic development. To encourage entrepreneurship and new jobs, towns and municipalities most often simplify regulations, reduce local taxes, and introduce various benefits and incentives. The contribution of the paper is manifested in providing useful guidance to local governments to improve the business environment.
Keywords: 330; business environment; business incentives; Croatia; entrepreneurship; local economic development; residents' quality of life